DC MOTOR ANGULAR POSITION CONTROL SYSTEM USING ARDUINO PLATFORM - Dragos-Ioan Matei; Alexandru Negroiu; Gabriela Bucur (Romanian Journal of Petroleum & Gas Technology)
The objective of this paper is to realize an angular position control system with a direct current motor. For this purpose, an Arduino microcontroller board is used to control the LS-25GA370 DC motor. The L298N dual H-bridge motor driver is used to modulate the PWM signal and control the travel direction. PID (proportional, integral and derivative) control algorithms are used to generate the PWM output. To implement a PID controller, the tuning parameters of the controller, namely proportional gain, integral gain and derivative gain must be carefully determined. Since the system is nonlinear, the PID controller is the best choice to accomplish this task. The sensor used was a Hall type encoder. To test the system, a LabVIEW interface was used, which communicates with the Arduino Uno platform through the serial port. This technical solution, using PID controller, can be applied for robotic arm position control system and many other industrial applications.